Ngữ pháp tiếng Anh - Mai Lan Hương; Nguyễn Thanh Loan. (Tp.HCM : Nxb Trẻ, 2000)
Tenses; Sequence of tenses; Clauses and phrases; Expressions of quantity; Styles; Emphasis; Reported speench; The active-passie voice; sentences....
Keywords: Anh ngữ; English Grammar; Anh ngữ -- Ngữ pháp